Platelet Function and Risk of Bleeding in Patients With Acute Coronary Syndrome Following Tirofiban Infusion - Li, Xiaoye; Zhang, Shuning; Wang, Zi; Ji, Qiuyi; Wang, Qibing; Li, Xiaoyu; Lv, Qianzhou (Frontiers in Pharmacology, 2019)
To assess platelet function and bleeding risks for acute coronary syndrome patients after infusion tirofiban. We enrolled 196 patients who were diagnosed as ACS according to guideline in cardiac intensive care unit between May 2016 and May 2017. Patients were allocated 1:1 to tirofiban and w/o tirofiban group. We applied thrombelastograghy to detect on-treatment platelet reactivity and laboratory test to assess bleeding risk. RESULTS: A total of 196 ACS patients who met inclusion and exclusion criteria were screened and equally allocated to two groups: 98 patients were assigned to receive tirofiban and 98 were not. Patients medication with tirofiban were in higher risk of left anterior descending culprit lesions (59.2% vs. 30.6%, P = 0.000). After infusion tirofiban, inhibition of platelet aggregation (IPA) induced by thromboxane A2 and adenosine diphosphate were significantly higher compared with w/o tifiban infusion (80.3±19.6% vs. 72.6±13.0%,P = 0.002 and 81.0±19.8% vs. 75.4±12.4%, P = 0.020, respectively). After administration of tirofiban, decrease of hemoglobin, hematocrit and platelet levels were not significantly different compared with baseline (P > 0.05). There was no significant difference between two groups with respect of Hb, Hct and PLT after infusion. The inflammation biomarker, C-reactive protein values were significant lower after infusion tirofiban compared with w/o tirofiban (11.9±14.2 vs. 17.9±21.2, P = 0.020). Within 1-year follow-up, there was no significant difference by tirofiban administration in terms of MACE occurrence ratio compared with w/o tirofiban (P = 0.208). The assessments of cardiac biomarkers showed that tirofiban could decrease incidence of procedural myocardial infarction with respect of 3–5 times normal as cardiac biomarkers (OR = 0.250, 95% CI: 0.067-0.925, P = 0.027). Also for the follow-up, the occurrence ratio of left atrial dilation refer to enlargement of left atrial diameter >40mm was lower compared with w/o tirofiban (OR = 0.533, 95%CI: 0.301-0.945, P = 0.031). CONCLUSION: Infusion tirofiban could lead to a significantly higher decrease of platelet activation for ACS patients. Meanwhile, administration tirofiban did not increase bleeding risk. No significant difference was found that concomitant medication tirofiban could decrease occurrence rate of MACE in 1-year follow-up.